Inter-observer and intra-observer agreement in the radiographic diagnosis of avascular necrosis of the femoral head following slipped capital femoral epiphysis - Davidson, Darin (Springer Berlin Heidelberg, 2010)
INTRODUCTION: Slipped capital femoral epiphysis (SCFE) is a common pediatric hip disorder. Avascular necrosis (AVN) of the femoral head is a devastating complication of SCFE. The frequency of this complication reported in the literature has been variable. It was the objective of this study to estimate the inter- and intra-observer agreement between two experienced pediatric orthopaedic surgeons for the radiographic diagnosis of AVN following SCFE. METHODS: A retrospective review of all cases of SCFE treated at our center between 1995 and 2005 was performed. All cases of AVN and a random sample of 19 of the remaining cases were selected for study. The most recent anteroposterior and lateral radiographs were presented to two experienced pediatric orthopaedic surgeons in a random order. Inter-observer reliability was determined by calculating the kappa statistic to assess for clinical agreement. Each observer repeated this process two weeks after the initial review. RESULTS: There were a total of 103 cases of SCFE, of which four were diagnosed with AVN. The inter-observer agreement in the first trial was 0.79. The intra-observer agreement for the first observer was 0.9 and for the second observer, it was 0.88. CONCLUSION: The agreement, both inter- and intra-observer, for the radiographic diagnosis of AVN amongst adolescents with previous SCFE is very high. The results of this study suggest that the reported discrepancy of AVN in the literature following SCFE is not likely due to the lack of inter- and intra-observer agreement.